Numerical Study of a Turbulent Single-Stage Axial Flow - Majid Almas (Journal of Advances in Applied & Computational Mathematics, 2016)
This paper studies the flow in an axial fan with a rotor in front and stators (vanes) in the rear. This configuration is typical of a single-stage axial flow turbo machine. The standard Â model with enhanced wall treatment. Interaction between these components is determined considering the rotor and stator together in a single calculation. Numerical calculations have been performed to investigate the effects of different angular velocities on pressure contours, mass flow rates and total pressure and the results have been shown and discussed through figures. The results show that the increase of angular velocity has a significant effect on the governing physical parameters.